Endogenous ligands of the aryl hydrocarbon receptor regulate lung dendritic cell function. Issue 1 (10th November 2015) - Thatcher, Thomas H.; Williams, Marc A.; Pollock, Stephen J.; McCarthy, Claire E.; Lacy, Shannon H.; Phipps, Richard P.; Sime, Patricia J.
Summary: The aryl hydrocarbon receptor (AhR) is a transcription factor that has been extensively studied as a regulator of toxicant metabolism. However, recent evidence indicates that the AhR also plays an important role in immunity. We hypothesized that the AhR is a novel, immune regulator of T helper type 2 (Th2) ‐mediated allergic airway disease. Here, we report that AhR‐deficient mice develop increased allergic responses to the model allergen ovalbumin (OVA), which are driven in part by increased dendritic cell (DC) functional activation. AhR knockout (AhR −/− ) mice sensitized and challenged with OVA develop an increased inflammatory response in the lung compared with wild‐type controls, with greater numbers of inflammatory eosinophils and neutrophils, greater T‐cell proliferation, greater production of Th2 cytokines, and higher levels of OVA‐specific IgE and IgG1. Lung DCs from AhR −/− mice stimulated antigen‐specific proliferation and Th2 cytokine production by naive T cells in vitro . Additionally, AhR −/− DCs produced higher levels of tumour necrosis factor‐ α and interleukin‐6, which promote Th2 differentiation, and expressed higher cell surface levels of stimulatory MHC Class II and CD86 molecules. Overall, loss of the AhR was associated with enhanced T‐cell activation by pulmonary DCs and heightened pro‐inflammatory allergic responses. This suggests that endogenous AhR ligands are involved in the normal regulation of Th2‐mediated immunity in the lung via a DC‐dependent mechanism. Therefore, the AhR may represent an important target for therapeutic intervention in allergic airways inflammation.